Analysis of the Preservation of the Pancasila Sports Hall in Surabaya as a Cultural Heritage Site According to Internasional Standards - Nanda, Nabila Berlian (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
The preservation of historic buildings in Indonesia is a critical issue in modern urban development. This study aims to analyze the potential for preserving the Pancasila Sports Hall in Surabaya as a cultural heritage site based on national and internasional standards. The research method employed is a descriptive qualitative approach utilizing literature review, conceptual observation, and analysis of cultural preservation regulations. The results of the study indicate that the GOR Pancasila holds significant value as a modern cultural heritage site that represents the development of sports, the city’s identity, and the collective memory of the people of Surabaya. Key challenges to its preservation include urban development pressures, a lack of documentation, limited public awareness, and weak enforcement of conservation policies. Therefore, a collaborative preservation strategy is needed involving the government, the community, academics, and the private sector through adaptive revitalization, the digitization of cultural documentation, and the strengthening of regulations for the protection of historic buildings. This study is expected to serve as a reference in the development of policies for the preservation of historic sports buildings in Indonesia in accordance with UNESCO principles and Law No. 11 of 2010 on Cultural Heritage